The Role of Blockchain Technology in Strengthening Innovative Accounting Practices: A Multidimensional Data-Driven Approach - Babaei, Fatemeh; Hosseini, Zahra Sadat; Salehi, Mehrdad; Moradi, Mehrdad (Business, Marketing, and Finance Open, 2024)
This study adopts a multidimensional approach grounded in grounded theory to examine the transformative role of blockchain technology in enhancing innovative accounting practices. The primary objective of the research is to analyze how blockchain influences the enhancement of financial transparency, the improvement of data accuracy, the support of intelligent auditing, and the strengthening of innovative competencies among accountants and financial managers. Using a qualitative methodology based on grounded theory principles, data were collected through semi-structured interviews with experts and analyzed across three stages of open, axial, and selective coding. This process resulted in the development of a conceptual model derived from real-world experiences. The findings indicate that blockchain technology has the potential to transform traditional accounting systems by enabling real-time transparency, reducing errors and financial fraud, and improving the quality of decision-making. Technological proficiency and professional creativity emerge as key factors in the successful implementation of this technology. Nevertheless, challenges such as infrastructural weaknesses, legal ambiguities, and cultural resistance continue to pose significant barriers. This study emphasizes that realizing the full potential of blockchain in accounting requires the formulation of targeted strategies, organizational readiness, and investment in the development of digital skills. The proposed conceptual model serves as a practical roadmap for policymakers, educational institutions, and financial organizations seeking to effectively leverage this emerging technology.